Restrictive spirometric pattern in the general adult population : Methods of defining the condition and consequences on prevalence - Backman, Helena; Eriksson, Berne; Hedman, Linnea; Stridsman, Caroline; Jansson, Sven-Arne; Sovijarvi, Anssi; Lindberg, Anne; Ronmark, Eva; Lundback, Bo (Respiratory Medicine, 2016)
Background: Attempts have been made to use dynamic spirometry to define restrictive lung function, but the definition of a restrictive spirometric pattern (RSP) varies between studies such as BOLD and NHANES. The aim of this study was to estimate the prevalence and risk factors of RSP among adults in northern Sweden based on different definitions. Methods: In 2008-2009 a general population sample aged 21-86y within the obstructive lung disease in northern Sweden (OLIN) studies was examined by structured interview and spirometry, and 726 subjects participated (71% of invited). The prevalence of RSP was calculated according to three different definitions based on pre-as well as post-bronchodilator spirometry: 1) FVC <80% & FEV1/FVC > 0.7 2) FVC <80% & FEV1/FVC > LLN 3) FVC <LLN & FEV1/FVC > LLN Results: The three definitions yielded RSP prevalence estimates of 10.5%, 11.2% and 9.4% respectively, when based on pre-bronchodilator values. The prevalence was lower when based on post-bronchodilator values, i.e. 7.3%, 7.9% and 6.6%. According to definition 1 and 2, the RSP prevalence increased by age, but not according to definition 3. The overlap between the definitions was substantial. When corrected for confounding factors, manual work in industry and diabetes with obesity were independently associated with an increased risk for RSP regardless of definition. Conclusions: The prevalence of RSP was 7-11%. The prevalence estimates differed more depending on the choice of pre-compared to post-bronchodilator values than on the choice of RSP definition. RSP was, regardless of definition, independently associated with manual work in industry and diabetes with obesity. (C) 2016 The Authors. Published by Elsevier Ltd. Peer reviewed